Is legal reasoning like medical reasoning?. (1st September 2014) - Samuel, Geoffrey
Abstract : In this paper, stimulated by the publication some years ago in France of a small book on medical reasoning, legal and medical reasoning are compared. The question that is asked is whether the differences between the two types of reasoning will permit one to have a better understanding of some of the methodological and epistemological issues associated with legal reasoning. It will be argued that although medical and legal reasoners do share things in common, legal reasoning, perhaps unlike medical reasoning, is actually concerned less with the explanation or even comprehension of texts or the facts of a dispute ( explicatio causæ ) and more with what will be termed the 'manipulation' of facts ( accommodatio factorum ). Lawyers purify and (or) construct 'virtual' factual situations out of perceived 'actual' factual situations in order to make them conform or not conform in an isomorphic way with factual situations implied by a legal text or precedent. Medical reasoning is equally complex but facts are read in a different way.